2013
DOI: 10.1118/1.4772075
|View full text |Cite
|
Sign up to set email alerts
|

Gafchromic EBT2 film dosimetry in reflection mode with a novel plan‐based calibration method

Abstract: Purpose: A dosimetric system formed by Gafchromic EBT2 radiochromic film and Epson Expression 10000XL flatbed scanner was commissioned for dosimetry. In this paper, several open questions concerning the commissioning of radiochromic films for dosimetry were addressed: a) is it possible to employ this dosimetric system in reflection mode; b) if so, can the methods used in transmission mode also be used in reflection mode; c) is it possible to obtain accurate absolute dose measurements with Gafchromic EBT2 films… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect. We have also not observed any significant difference in the accuracy of the two modes as long as the appropriate procedures were followed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect. We have also not observed any significant difference in the accuracy of the two modes as long as the appropriate procedures were followed.…”
Section: Discussionmentioning
confidence: 97%
“…While the use of reflective mode for the film scanning under Bouchard's protocol is not in common use, reflective mode has been examined in previous papers 20 , 21 to produce comparable results to transmission mode (22) . While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some discrepancies occur in the inferior part of the 250 cGy isodose line, but the dose gradient here are not steep. EBT2 ilm has been proven to be accurate at measuring dose distributions (12) . Since XR-RV3 results compares well with EBT2 ilm in this study, it implies satisfactory accuracy as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results 18 found better fit when lateral corrections are absolute corrections independent of dose, and sensitometric curves are polynomial fits of order four. Hence, lateral corrections were calculated as…”
Section: A Channel-independent Perturbationsmentioning
confidence: 99%
“…They also compared different single, dual and triple channel methods, and found better agreement between planned and calculated dose distributions using the average dose of all three channels in comparison to using the channel-independent perturbations method. In an earlier article 18 , our group suggested calculating the film dose as the weighted mean dose of all three channels. For each channel, the inverse of the mean square error obtained during the film calibration was used as weight.…”
Section: Introductionmentioning
confidence: 99%